Effect of Multi-Walled Carbon Nanotubes on Infill Material for Pipeline Composite Repair - Arifin, Hanis Hazirah; Zardasti, Libriati; Yahaya, Nordin; Lim, Kar Sing; Abd Khalid, Nur Hafizah; Abd Latif, Siti Asma; Md Noor, Norhazilan (International Journal of Integrated Engineering, 2022)
The properties of the infill material are an important parameter in predicting the performance and behaviour of Fibre Reinforced Polymer (FRP) composite for effective design. This paper identifies the potential of Multi-walled Carbon Nanotubes (MWCNTs) as nanofiller in enhancing the performance of infill material. Two compositions of MWNTs at 0.1% and 0.5% of weight fractional were evaluated toward neat epoxy on tensile and lap shear test. By comparing MWCNTs-based modified epoxy grouts and neat epoxy grout, a significant increase in tensile strength was observed, especially with 0.5% of MWCNTs by almost 53.3%. While the inclusion of MWCNTs showed a comparable increment in shear strength in both 0.1% and 0.5% weight fractional by 13%. The image of morphologies showed that MWCNTs were well incorporated into the matrix, making the cross-section of the fracture rougher by sharing stress. This shows the potential of the MWCNTs in changing the properties of the modified epoxy grout, provided that the MWCNTs are appropriately dispersed throughout the resin matrix.